Publication Trends and Development of Critical Thinking Concepts in Elementary Education: A Bibliometric Review - Maria Oktaviani, Anna; Marini, Arita; Supena, Asep (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Critical thinking is becoming an increasingly important skill in the 21st century, characterized by technological advances, globalization, and information complexity. To determine research trends related to critical thinking skills, this research uses the R Package and carries out bibliometric analysis. The metadata used comes from SCOPUS from 2014 to 2024. The data was analyzed with the keywords